Living Inside and Outside the Trenches in Le Cœur des Batailles: A Textual and Graphic Analysis of "La Marne" and "Verdun" by Jean-David Morvan, Igor Kordey, and Walter - Cirella-Urrutia, Anne (Status Quaestionis, 2021)
–